Non-shoulder Injuries in Swimming: A Systematic Review. Issue 3 (1st May 2022) - Hill, Lee; Mountjoy, Margo; Miller, Jim
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: The shoulder is the most common injury in swimming, followed by the knee and spine. The repetitive nature of swimming training may predispose a swimmer to injury. Several risk factors have been previously identified, but the level of evidence and level of certainty that these risk factors predispose a swimmer to injury risk has yet to be evaluated critically in a systematic review. Design: Systematic review and meta-analysis following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data Sources: Data were obtained through PubMed, Cochrane, and Google Scholar. The database search was limited to articles that were published between January 1980 and December 2019. Eligibility Criteria for Selecting Studies: Level I, II, and III studies were included in this review. All studies must have been conducted in swimmers or swimming, a description of the specific pathology and provide at least one identified risk factor with an association ( P < 0.05). Results: A total of 19 critically appraised articles identified 28 potential risk factors for musculoskeletal injuries in swimmers. The risk factors were grouped by the anatomical region: neck and back, pelvis and hip, and the knee. Only 2 risk factors were appraised at a moderate level of certainty, both occurring in the knee. The remaining 26 identified risk factors were appraised at a low level of certainty. There is a clear lack of research surrounding nonshoulder injuries in swimmers.